IMPLEMENTASI UNDANG-UNDANG NOMOR 44 TAHUN 2008 TENTANG PORNOGRAFI DAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM PENANGGULANGAN TINDAK PIDANA PORNOGRAFI OLEH POLRES BULELENG - Gusti Ayu Christina Ira Yanti; Dewa Gede Sudika Mangku; I Wayan Kertih (Universitas Pendidikan Ganesha, 2023)
This study aims to determine and analyze the factors that influence the occurrence of mayantara pornography crime and the efforts made by the Buleleng Regional Police in preventing and overcoming mayantara pornography crime in the Buleleng Regency area. This study used a type of empirical juridical research. Data collection techniques are carried out by means of document studies and interviews with Ps. Kaurmintu of the Criminal Investigation Unit of the Buleleng Police, where later the data obtained will be analyzed in a qualitative descriptive manner. From the results of the study, it was obtained that the factors that cause pornography crimes are internal factors and external factors. Internal factors include the individual himself and his family, while external factors include environmental influences, advances in information technology, laws governing pornography and law enforcement. In preventing and tackling pornography crimes, the Buleleng Regional Police made various efforts to overcome this pornography crime. The Buleleng Police conducted investigations and investigations into pornography crimes that occurred in the Buleleng Regency area, in these investigations and investigations the Buleleng Police collaborated with Internet Service Providers (ISPs) and carried out cyber media surveillance or cyber patrols.